Baseline neuropsychological profiles in prion disease predict survival time. Issue 9 (9th September 2020) - Sundaram, Saranya E.; Staffaroni, Adam M.; Walker, Nicole C.; Casaletto, Kaitlin B.; Casey, Megan; Golubjatnikov, Aili; Metcalf, Stacy; O'Leary, Kelly; Wong, Katherine; Benisano, Kendra; Forner, Sven; Gonzalez Catalan, Marta; et al.
Abstract: Objective: Few studies have captured the neuropsychological profile of sporadic Creutzfeldt–Jakob disease (sCJD) with neuropsychological testing, and little is known about cognitive predictors of survival. We characterized baseline neuropsychological performance in sCJD and investigated associations with survival. Methods: sCJD participants who completed the MMSE ( n  = 118), 61 sCJD of whom also completed a neuropsychological battery at baseline, and 135 age‐matched healthy controls, were included. Composite scores of global cognition, memory, executive functions, visuospatial, and language were derived. Cox proportional hazard models estimated survival time, controlling for age and education. Additional models adjusted for Barthel Index and PRNP codon 129 polymorphism. Results: sCJD participants performed significantly worse than controls on all cognitive tasks and composites with most showing very large effect sizes. The three tests showing the largest group differences were delayed verbal recall (Hedges' g  = 4.08, P  < 0.0001), Stroop Inhibition (Hedges'g = 3.14, P  < 0.0001), and Modified Trails (Hedges'g = 2.94, P  < 0.0001). Memory (95%) and executive functioning (87%) composites were most commonly impaired. Poorer global (HR = 0.65, P  < 0.0001), visuospatial (HR = 0.82, P  < 0.0001), and memory (HR = 0.82, P  = 0.01) composites predicted shorter survival. Visuospatial cognition remained a significant predictor even after adjusting for all other cognitive composites; each standard deviation decrease in visuospatial cognition was associated with an 18% higher chance of death (HR = 0.82, P  < 0.003). Global (HR = 0.68, P  = 0.03) and visuospatial (HR = 0.82, P  = 0.001) composites remained significant predictors after controlling for Barthel Index and codon 129. Interpretation: sCJD participants exhibit a broad range of cognitive impairments, with memory and executive functioning deficits in the vast majority. Neuropsychological assessment, particularly of visuospatial abilities, informs prognostication in sCJD.